(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the implementation of an implicit learning approach for teaching tourism-specific terminology, leveraging information technologies to facilitate incidental acquisition of vocabulary. We contrast implicit learning with traditional explicit methods, review relevant literature in tourism education and e-learning, and propose a blended‑learning instructional model. A pilot study with tourism students evaluates the efficacy of embedded terminology in interactive digital environments. Results suggest improved retention, fluency in usage, and learner motivation. Recommendations for integrating immersive tools, scaffolding, and multimodal content are provided for practitioners and researchers.